2012
DOI: 10.1089/pho.2011.3171
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Physiotherapy and GaAlAs Laser in the Management of Temporomandibular Joint Disorders

Abstract: The laser therapy was effective in the improvement of the range of temporomandibular disorders (TMD) and promoted a significant reduction of pain symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 16 publications
8
31
0
12
Order By: Relevance
“…Statistically significant reduction of pain in the laser group in relation to the placebo was observed in research by Gray et al 13 , Bertolucci and Grey 14 , Fikácková et al 15 , Mazzetto et al 16 , Öz S et al 17 , Çetiner et al 18 and Venezian et al 19 . Some of the studies reported both reduction of pain as well as a significant improvement in the range of mandibular movements and decreased tenderness of masticatory muscles [20][21][22] . Previous studies suggest that both idiopathic TN and idiopathic BMS may be of neuropathic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant reduction of pain in the laser group in relation to the placebo was observed in research by Gray et al 13 , Bertolucci and Grey 14 , Fikácková et al 15 , Mazzetto et al 16 , Öz S et al 17 , Çetiner et al 18 and Venezian et al 19 . Some of the studies reported both reduction of pain as well as a significant improvement in the range of mandibular movements and decreased tenderness of masticatory muscles [20][21][22] . Previous studies suggest that both idiopathic TN and idiopathic BMS may be of neuropathic origin.…”
Section: Discussionmentioning
confidence: 99%
“…TMR, başlıca semptomları kas ve eklem ağrıları, alt çene hareketleri ve ağız açıklığında kısıtlanma ve eklem sesleri olan multifaktöriyel durumlardır (2). Toplumun %40'ından fazlası bu belirtilerin en az birine sahiptir fakat bunların sadece dörtte biri bu belirtilerin farkındadır ve %10-20'si tedavi gereksinimi duymaktadır (3). Psikolojik faktörler, okluzal dengesizlikler ve parafonksiyonel alışkanlıklar altta yatan başlıca etkenlerdir (4).…”
Section: Introductionunclassified
“…A terapia com laser de baixa intensidade (LLLT), assim como a TMO, é um tratamento não invasivo que tem mostrado ser benéfico no tratamento de dor relacionado à DTM sendo, portanto, considerado eficiente como agente terapêutico e coadjuvante no tratamento das DTM (Kulekcioglu et al, 2003;De Medeiros et al, 2005;Çetineret al, 2006;Mcnelly et al, 2006;Medlicott e Harris, 2006;Shinozaki et al, 2006;Fikácková et al, 2007;Mazzetto et al, 2007;Carrasco et al, 2008;Shirani et al, 2009;Marini et al, 2010;Venezian et al, 2010;Mazzetto et al, 2010;Oz et al, 2010;Dostalová et al, 2012;Sattayut et al, 2012;de Moraes Maia et al, 2014;Salmos-Brito et al, 2013;Melchior et al, 2013;Ahrari et al, 2014;Herpich et al, 2015;Rodrigues et al, 2015).…”
Section: Tomados Em Conjunto Os Resultados Atuais Indicam Que O Protunclassified
“…A terapia com laser de baixa intensidade (LLLT) é um tratamento não invasivo que tem mostrado ser benéfico no tratamento de dor relacionado à DTM sendo, portanto, considerado eficiente como agente terapêutico e coadjuvante no tratamento das DTM (Kulekcioglu et al, 2003;De Medeiros et al, 2005;Çetiner et al, 2006;Mcnelly et al, 2006;Medlicott e Harris, 2006;Shinozaki et al, 2006;Fikácková et al, 2007;Mazzetto et al, 2007;Carrasco et al, 2008;Shirani et al, 2009;Marini et al, 2010;Venezian et al, 2010;Mazzetto et al, 2010;Öz et al, 2010;Dostalová et al, 2012;Sattayut e Bradley et al, 2012;Salmos-Brito et al, 2013;Melchior et al, 2013;de Moares Maia et al, 2014;Ahrari et al, 2014;Herpich et al, 2015;Rodrigues et al, 2015) e no alívio de dor cervical crônica (Chow et al, 2006). Além disso, há relatos de melhora da amplitude dos movimentos mandibulares (Kulekcioglu et al, 2003;Çetiner et al, 2006;Núñez et al, 2006;Mazzetto et al, 2010;Gökçen-Röhlig et al, 2012;Ahrari et al, 2014;Rodrigues et al, 2015), da dificuldade para mastigar (Çetiner et al, 2006) e eficiência mastigatória após a LLLT (de Moraes Maia et al, 2014).…”
Section: Laserterapiaunclassified